Assessment of BoHV-4-based vector vaccine intranasally administered in a hamster challenge model of lung disease - Park, Seok-Chan; Conti, Laura; Franceschi, Valentina; Oh, Byungkwan; Yang, Myeon-Sik; Ham, Gaeul; Di Lorenzo, Antonino; Bolli, Elisabetta; Cavallo, Federica; Kim, Bumseok; Donofrio, Gaetano (Frontiers in Immunology, 2023)
Bovine herpesvirus 4 (BoHV-4) is a bovine Rhadinovirus not associated with a specific pathological lesion or disease and experimentally employed as a viral vector vaccine. BoHV-4-based vector (BoHV-4-BV) has been shown to be effective in immunizing and protecting several animal species when systemically administrated through intramuscular, subcutaneous, intravenous, or intraperitoneal routes. However, whether BoHV-4-BV affords respiratory disease protection when administered intranasally has never been tested. In the present study, recombinant BoHV-4, BoHV-4-A-S-ΔRS-HA-ΔTK, was constructed to deliver an expression cassette for the SARS-CoV-2 spike glycoprotein, and its immunogenicity, as well as its capability to transduce cells of the respiratory tract, were tested in mice. The well-established COVID-19/Syrian hamster model was adopted to test the efficacy of intranasally administered BoHV-4-A-S-ΔRS-HA-ΔTK in protecting against a SARS-CoV-2 challenge. The intranasal administration of BoHV-4-A-S-ΔRS-HA-ΔTK elicited protection against SARS-CoV-2, with improved clinical signs, including significant reductions in body weight loss, significant reductions in viral load in the trachea and lungs, and significant reductions in histopathologic lung lesions compared to BoHV-4-A-S-ΔRS-HA-ΔTK administered intramuscularly. These results suggested that intranasal immunization with BoHV-4-BV induced protective immunity and that BoHV-4-BV could be a potential vaccine platform for the protection of other animal species against respiratory diseases.